PENINGKATAN HASIL BELAJAR SISWA PADA PEMBELAJARAN MATEMATIKA MENERAPKAN KETERAMPILAN PROSES DI KELAS V - Nurhayani, Nurhayani; Tampubolon, Budiman; Asran, Mastar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the use of process skills in improving student learning outcomes in the fifth grade Mathematics learning at State Elementary School 04 Pontianak West. This study uses a descriptive method with a form of classroom action research. The nature of research is collaborative. The research took place at the State Elementary School 04 Pontianak Barat with the subject of the research were students of class V which numbered 34 people. Data collection techniques using interview techniques, direct observation techniques, measurement techniques. Data collection tool is the observation sheet. Data analysis uses calculation of percentages and averages. The ability of teachers to develop learning plans applying process skills has increased in each cycle, in cycle 1 which is 3.37 increased in cycle 2 to 3.58 and in cycle 3 has increased to 3.78. The ability of teachers to implement learning to apply process skills in class V has increased. In cycle 1 the average value was 3.41, cycle 2 increased to 3.58, and cycle 3 increased to 3.72. Student learning outcomes in mathematics learning apply process skills to increase, cycle 1 the average value of 65.88 and cycle 2 increases by 20.33 to 86.21.Â Â Keywords:Learning Outcomes, Process Skills, and Mathematics